Association of periodontitis with cerebral small vessel disease in hypertensive patients - A pilot study - Tiago Pinto-Ribeiro; António Felino; Ricardo Faria-Almeida; Ana Monteiro; Jorge Polónia (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2024)
Objectives: Cerebral small vessel disease is a chronic, progressive disorder of arterioles, capillaries, and small veins supplying the brain's white matter and deep structures of gray matter. The latest evidence seems to suggest that chronic oral infections such as periodontitis contribute to cerebral small vessel disease progression. This study evaluated the relationship between periodontal disease and brain white matter hyperintensities. Methods: Forty-three hypertensive patients, aged between 38-82, without previous cardiovascular events, of which 42% were female and 50% diabetic, were evaluated. An association between mean probing depth, mean attachment level, bleeding on probing, total periodontal inflamed surface area, and white matter hyperintensities diagnosed by magnetic resonance was studied. A significance level (α) of 0.05 was considered, and Pearson's chi-square and Mann-Whitney tests were applied. Results: Data analysis revealed an inverse correlation between mean probing depth, bleeding on probing, total periodontal inflamed surface area, and white matter hyperintensities. A positive correlation was found between mean attachment level and white matter hyperintensities. Conclusions: In our study and within our sample, lower values of mean probing depth, bleeding on probing, and total periodontal inflamed surface area were associated with more white matter hyperintensities. Contrarily, mean attachment level was positively associated with white matter hyperintensities.